Repair of cartilage defects in osteoarthritis rats with induced pluripotent stem cell derived chondrocytes. Issue 1 (December 2016) - Zhu, Yanxia; Wu, Xiaomin; Liang, Yuhong; Gu, Hongsheng; Song, Kedong; Zou, Xuenong; Zhou, Guangqian
Abstract Background The incapacity of articular cartilage (AC) for self-repair after damage ultimately leads to the development of osteoarthritis. Stem cell-based therapy has been proposed for the treatment of osteoarthritis (OA) and induced pluripotent stem cells (iPSCs) are becoming a promising stem cell source. Results Three steps were developed to differentiate human iPSCs into chondrocytes which were transplanted into rat OA models induced by monosodium iodoacetate (MIA). After 6 days embryonic body (EB) formation and 2 weeks differentiation, the gene and protein expression of Col2A1, GAG and Sox9 has significantly increased compare to undifferentiated hiPSCs. After 15 weeks transplantation, no immune responses were observed, micro-CT showed gradual engraftment and the improvement of subchondrol plate integrity, and histological examinations demonstrated articular cartilage matrix production. Conclusions hiPSC could be an efficient and clinically translatable approach for cartilage tissue regeneration in OA cartilages.